Creation of an integrated risk classification system for large events within the Military Police of Alagoas as a tool to support civil disturbance control (Research, Society and Development, 2026)
This study aims to develop an integrated risk classification system for large events within the Military Police of Alagoas as a tool to support civil disturbance control. The research is applied in nature, with a qualitative approach, based on bibliographic review, document analysis, and operational experience. The proposed model is structured around key variables — such as event type, public profile, history of occurrences, alcohol consumption, location characteristics, and social context — organized into a scoring system for risk classification. The results indicate that the use of objective criteria reduces subjectivity in decision-making, improves operational planning, optimizes resource allocation, and strengthens preventive actions. Furthermore, the system contributes to aligning police actions with the proportional use of force and the preservation of public order. It is concluded that the adoption of structured risk management tools represents a significant advancement in the modernization of police operational practices.